PROBLEMS, MAIN DIRECTIONS AND PROSPECTS FOR THE DEVELOPMENT OF THE DIGITAL ECONOMY IN UZBEKISTAN - Makhmudova, Gulzhakhon Nematdzhonovna; Karimov, Diyor Mukhtarovich; Kholmatov, Sirojiddin Islomjon Ugli (Journals Park Publishing, 2023)
The scientific article “Problems, main directions and prospects for the development of the digital economy in Uzbekistan” explores the evolution of the digital economy in Uzbekistan, highlighting the key directions of this process. The measures taken by the government are considered, including the implementation of the National Concept of the Digital Economy and the “Digital Uzbekistan – 2030” strategy. Covers changes in the telecommunications industry, the level of public trust in digital services, and efforts to train qualified personnel in the field of digital technologies. The article also raises problems that slow down the digitalization process, such as uneven distribution of digital infrastructure, challenges in ensuring cybersecurity and others. Despite these challenges, the article highlights the potential of the digital economy to improve quality of life, increase productivity and create new business opportunities in Uzbekistan. The outlook includes deepening digital transformation in various sectors and supporting innovation to drive sustainable and dynamic development of the country.
Keywords: digital economy, investments, digital technologies, e-government, e-commerce, information and communication technologies (ICT)